Thermophysical properties and heat transfer performance of TiO2-Distilled water nanofluid using shell and tube heat exchanger - Permanasari, A.A. (Institute of Electrical and Electronics Engineers Inc., 2019)
To date, there is a rise of interest in utilizing nanofluid as an alternative cooler to replace the conventional one. Therefore, this study aimed to find out the effect of adding nanoparticle into a working fluid on its thermophysical properties and heat transfer performance using the laboratory-scaled shell and tube heat exchangers with titanium dioxide (TiO2) as the nanoparticle. The diameter of the dispersed TiO2 was 30 nm. This research utilized distilled water as the base fluid. The thermophysical properties value of nanofluid dispersed with TiO2 had better value compared to the conventional working fluid such as lubricant/oil. This research divided the nanoparticle into four fractions: 0.025 volume, 0.05 volume, 0.075 volume, and 1 volume. The synthesize process used two-step method by adding nanoparticle into the base fluid then mixing it using magnetic stirrer for 30 minutes and ultrasonic sonicator for 2 hours. The cold-water volumetric flow rate in the heat exchanger was 0.5 LPM, 1 LPM, 1.5 LPM. The result showed that TiO2-distilled water nanofluid with 1 nanoparticle concentration in 1.5 LPM water volumetric flow rate had the heat energy value of 94.4, larger compared to the heat energy of distilled water only. Â© 2019 IEEE.